Hybrider le climat et les luttes - Berthier, Aurélien; Mourin, Barbara (Agir par la culture, 2018)
Le concept d’intersectionnalité définit les points de rencontre entre des luttes contre les dominations liées à la classe sociale, à la racisation ou au genre. Il a permis réflexions et nouveaux champs de bataille féconds. Activistes et intellectuel·les proposent de continuer à multiplier les hybridations entre ces combats sociaux, culturels et politiques avec les luttes environnementales et climatiques. Prenant... View Article
Keywords: approches et analyses; capitalisme; environnement; intersectionnalité; justice sociale; militance; patriarcat; projet charge mentale; ressource en ligne; systèmes d'oppressions; thématiques; écoféminisme

Sentir-penser avec la Terre: l'écologie au-delà de l'Occident - Escobar, Arturo; Andrade Pérez, Roberto; Bonvalot, Anne-Laure; Bordai, Ella; Bourguignon, Claude; Colin, Philippe; Bednik, Anna (Éditions du Seuil, 2018)
"Les avancées récentes de l'anthropologie l'ont amplement démontré : la partition nature/culture qui fonde l'ontologie moderne occidentale et qui s'est imposée partout n'est pas la seule façon d'être au monde, encore moins la forme ultime de la civilisation. Un tel dualisme, qui sépare corps et esprit, émotion et raison, sauvage et civilisé, acteur et chercheur, humains et autres qu'humains, nous empêche de nous vivre comme partie du monde et nous conduit à le détruire. Dès lors, le projet émancipateur ne saurait se limiter à " changer le monde ". Il s'agit aujourd'hui de changer de monde. Des mouvements indigènes du Sud aux "zones à défendre" (ZAD) du Nord, les conflits politiques renvoient à des visions divergentes quant à la composition du monde et aux façons d'en prendre soin. Autrement dit, à un conflit ontologique. Comment, à l'heure de la crise écologique et face à l'échec de la mondialisation, penser cette dimension ontologique de la politique? Comment engager notre transition, en dialogue avec luttes des peuples non-occidentaux et les cosmologies non-modernes, pour habiter en conscience le plurivers, ce monde des mondes qu'est notre planète?"– Résumé de l'éditeur.
Section: 225 pages : illustrations ; 19 cm.
Keywords: anthropologie; approches et analyses; capitalisme; com5170; cours; crise écologique; discipline; environnement; justice sociale; ontologie; premier cycle; sciences humaines; système colonial; systèmes d'oppressions; thématiques; écologie

The Institution of Gender-Based Asylum and Epistemic Injustice: A Structural Limit - Sertler, Ezgi (Feminist Philosophy Quarterly, 2018)
One of the recent attempts to explore epistemic dimensions of forced displacement focuses on the institution of gender-based asylum and hopes to detect forms of epistemic injustice within assessments of gender related asylum applications. Following this attempt, I aim in this paper to demonstrate how the institution of gender-based asylum is structured to produce epistemic injustice at least in the forms of testimonial injustice and contributory injustice. This structural limit becomes visible when we realize how the institution of asylum is formed to provide legitimacy to the institutional comfort the respective migration courts and boards enjoy. This institutional comfort afforded to migration boards and courts by the existing asylum regimes in the current order of nation-states leads to a systemic prioritization of state actors’ epistemic resources rather than that of applicants, which, in turn, results in epistemic injustice and impacts the determination of applicants’ refugee status.
Keywords: approches et analyses; capitalisme; confort institutionnel; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; institutions; migration; philosophie; politiques migratoires; racisme; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

The gendered discourse of work-family balance in the oil and gas industry - Williams, Christine L. (Social Currents, 2018)
U.S. corporations have been slow to adopt family-friendly workplace accommodations, despite decades of research demonstrating their value. Some hope that the millennial generation will spur corporate change because, compared with older generations of workers, young people purportedly strive for more balanced lifestyles and gender equality in their relationships. This study examines the experiences of early career scientists and engineers employed by a major oil and gas corporation that has not implemented family-friendly accommodations, asking whether these highly trained workers seek work-family balance and whether they parlay these desires into requests for accommodation from their employer. Interviews reveal a gendered discourse of work-family balance at this firm: mothers and prospective mothers describe intense work-family conflict, but they blame themselves and not their employer. A number of men, in contrast, express satisfaction with their work-family balance, yet their narratives reveal that their achievement of balance depends on a traditional gender division of labor in the home. Some men and women seek alternative forms of balance that do not involve family; if thwarted from pursuing this goal, they are inclined to exit the company. These discourses of balance reflect neoliberal assumptions, reproduce gender inequality, and suggest the need for an alternative to the voluntary approach to promoting work-family policies. © 2017, © The Southern Sociological Society 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; conciliation famille-travail; discipline; famille; industrie pétrolière; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; états-unis